2020
DOI: 10.1108/jstpm-03-2020-0046
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the influence of transparency on the adoption of e-Government in Indonesia

Abstract: Purpose The purpose of this paper is to extend and validate the unified theory of acceptance and use of technology (UTAUT) for investigating the effect of transparency on the adoption of e-Government in Indonesia from the perspective of citizens. Design/methodology/approach A comprehensive review of the related literature leads to the development of a transparency-focused conceptual model to better understanding the adoption of e-Government. Structural equation modelling is used for analysing the data collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
12

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 40 publications
1
42
0
12
Order By: Relevance
“…Likewise, the existing technology ethics can increase work productivity, so the users' ability to adopt technology is higher. Previous literature has shown that performance expectancy has a significant impact on behavior intention (Eneizan et al, 2019;Khalilzadeh et al, 2017;Mohd Thas Thaker et al, 2021;Musyaffi, 2020;Rosnidah et al, 2019;Sabani, 2020;Sabbir et al, 2020;Sivathanu, 2019;Wiafe et al, 2019;Xu et al, 2019). Meanwhile, effort expectancy has a strong influence on performance expectancy and behavior intention (Arfi et al, 2021;Eneizan et al, 2019;Merhi et al, 2019;Mohd Thas Thaker et al, 2021;Musyaffi, 2020;Musyaffi et al, 2021;Rahi & Abd.…”
Section: Utautmentioning
confidence: 96%
“…Likewise, the existing technology ethics can increase work productivity, so the users' ability to adopt technology is higher. Previous literature has shown that performance expectancy has a significant impact on behavior intention (Eneizan et al, 2019;Khalilzadeh et al, 2017;Mohd Thas Thaker et al, 2021;Musyaffi, 2020;Rosnidah et al, 2019;Sabani, 2020;Sabbir et al, 2020;Sivathanu, 2019;Wiafe et al, 2019;Xu et al, 2019). Meanwhile, effort expectancy has a strong influence on performance expectancy and behavior intention (Arfi et al, 2021;Eneizan et al, 2019;Merhi et al, 2019;Mohd Thas Thaker et al, 2021;Musyaffi, 2020;Musyaffi et al, 2021;Rahi & Abd.…”
Section: Utautmentioning
confidence: 96%
“…Penelitian terkait e-Gov telah banyak dilakukan, di antaranya tentang persyaratan yang diperlukan untuk aplikasi e-Gov, pengaruh e-Gov terhadap kualitas pelayanan publik, evaluasi kepuasan terkait kualitas aplikasi e-Gov, menemukenali hambatan yang dihadapi dari sisi masyarakat dan pegawai, manajemen risiko operasional e-Gov, mengukur tingkat kesiapan, dan masih banyak lagi (Abdulrahman & Abdulrahman, 2015;Chaidir et al, 2020;Dewi et al, 2018;Feoh et al, 2015;Hamed et al, 2018;Mulyani et al, 2018;Purwadi, 2016;Putri, 2015;Sabani, 2020;Setiyorini et al, 2018;Supriyanto & Mustofa, 2016). Penelitian lain telah dilakukan di Kabupatan Sragen untuk mengetahui implementasi praktik pelaksanaan e-Gov.…”
Section: Pendahuluanunclassified
“…E-Government (e-Gov) pada dasarnya adalah pemanfaatan dan pendayagunaan Teknologi Informasi dan Komunikasi (TIK), terutama aplikasi, yang dipergunakan untuk pelayanan publik sebagai upaya untuk meningkatkan hubungan antara pemerintah, kalangan bisnis, dan masyarakat dengan cara memperbaiki kualitas layanan publik, meningkatkan efisiensi, efektivitas, akuntabilitas, dan transparansi penyelenggaraan pemerintahan (Abdulrahman & Abdulrahman, 2015;Albuquerque et al, 2017;BAKÓ, 2016;Chaidir et al, 2020;Goulas et al, 2016;Hamed et al, 2018;Hassan & Lee, 2015;Nainggolan, 2020;Ouchetto et al, 2015;Purwadi, 2016;Putri, 2015;Sabani, 2020;Setiyorini et al, 2018;Supriyanto & Mustofa, 2016). Hal ini dilakukan untuk meningkatkan kepercayaan dan memenuhi tuntutan masyarakat yang menaruh harapan besar terhadap pemerintah dalam hal pelayanan publik yang lebih baik dengan pemanfaatan TIK sehingga dapat mempercepat dan mempermudah pelayanan.…”
Section: Konsep E-governmentunclassified
See 2 more Smart Citations